Methotrexate dosage as a source of bias in biological trials in rheumatoid arthritis: a systematic review. Issue 9 (18th April 2016) - Durán, Josefina; Bockorny, Margarita; Dalal, Deepan; LaValley, Michael; Felson, David T
Abstract : Objectives: To evaluate if optimal dose of either oral or injectable regimens of methotrexate (MTX) of 25 mg/week was used in the comparator arms of studies comparing biologic drugs with MTX in rheumatoid arthritis (RA). Methods: A systematic literature search was carried out in MEDLINE, EMBASE and the Cochrane Library databases for randomised controlled trials comparing biologics with MTX in RA. A systematic review was performed among studies that met predefined criteria focusing on assessment of dose of MTX used in the comparator arm. Study authors were contacted when necessary. Study quality was assessed. Results: A total of 3276 references were identified and 13 trials were included. We obtained maximal dose and regimen for all. The maximal dose of MTX used in the comparator arm of the trials was no more than 20 mg/week in any trial and for all but one trial, MTX was given orally and not by injection. The trial that used an injectable form reached a maximum of 15 mg/week. Conclusions: A suboptimal dose of MTX was used in biological clinical trials performed in RA, particularly regarding route of administration. This may have biased findings in favour of biological agents.